The Using of Maslahah Mursalah Method as Hujjah - Muh. Idris; Finsa Adhi Pratama; Lian Mulyani Muthalib (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
After the death of the Prophet Sallallahu 'alaihi Wasallam, all the problems of Muslims are submitted to the scholars to look up for solutions from texts. The scholars are required to perform ijtihad in order to solve the problems arised by digging into the values of the text of the Qur'an and Hadith, in which the ijtihad will develop into ijtihad bir-ra'yi if the solutions cannot be found in the texts. There have been numerous methods used to deeply explore the laws such as ijma', qiyas, as well as istidlal like Istishab, Maslahah Mursalah, Al-Ihtihsan, Qoulu Shohaby, Syadd ad-Dzaro'i, Dilalah al-Iqtiran, Dilalah al-Ilham, Ru'yan of Prophet Sallallahu ‘alaihi Wasallam, and Syar’u Man Qoblana. All decisions from Allah Ta'ala definitely has the benefit value as it is impossible for Allah Ta'la to make a decision that is in vain. Starting from these values then born the Istimbath which is Maslahah Mursalah law. So, this discussion focuses on the meaning of maslahah mursalah, the background for the birth of the maslahah mursalah method, the division of maslahah mursalah, and the validity of maslahah mursalah as istidlal in ushul fiqh. This study uses literature review method by relying on the strength of references and strong analysis of literacy texts. The conclusion that can be drawn from this discussion is that maslahah mursalah is something that is beneficial for humans as the goal of syara'. There are differences of opinion regarding the position of maslahah mursalah in Islamic law, in which some accept it and some reject it to be used as hujjah. However, the two of them met at the point that the groups that reject is the maslahah that only based on lust and mind, they do accept maslahah as hujjahif it is in line with what is required by syara'.